2012
DOI: 10.1289/ehp.1103979
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mitochondrial DNA Copy Number in Occupations Associated with Low-Dose Benzene Exposure

Abstract: Background: Benzene is an established leukemogen at high exposure levels. Although low-level benzene exposure is widespread and may induce oxidative damage, no mechanistic biomarkers are available to detect biological dysfunction at low doses.Objectives: Our goals were to determine in a large multicenter cross-sectional study whether low-level benzene is associated with increased blood mitochondrial DNA copy number (mtDNAcn, a biological oxidative response to mitochondrial DNA damage and dysfunction) and to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 44 publications
1
51
0
Order By: Relevance
“…However, these studies have reported somewhat inconsistent results, possibly owing to variations in exposure concentration, exposure duration, type of exposure, and the dynamic balance between oxidative damage and anti-oxidative defense pathways. 20,21,34,35 For instance, exposure to low-level benzene and short-term exposure to traffic pollution were associated with increased mtDNA abundance, probably due to an adaptive biogenesis response to compensate moderate oxidative damage. 21,34 On the other hand, in an occupational setting where participants were exposed to high levels of elemental carbon and PM 10 (particulate matter with aerodynamic diameter ≤10 μm), Pavanello et al reported decreased levels of mtDNA abundance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies have reported somewhat inconsistent results, possibly owing to variations in exposure concentration, exposure duration, type of exposure, and the dynamic balance between oxidative damage and anti-oxidative defense pathways. 20,21,34,35 For instance, exposure to low-level benzene and short-term exposure to traffic pollution were associated with increased mtDNA abundance, probably due to an adaptive biogenesis response to compensate moderate oxidative damage. 21,34 On the other hand, in an occupational setting where participants were exposed to high levels of elemental carbon and PM 10 (particulate matter with aerodynamic diameter ≤10 μm), Pavanello et al reported decreased levels of mtDNA abundance.…”
Section: Discussionmentioning
confidence: 99%
“…20,21,34,35 For instance, exposure to low-level benzene and short-term exposure to traffic pollution were associated with increased mtDNA abundance, probably due to an adaptive biogenesis response to compensate moderate oxidative damage. 21,34 On the other hand, in an occupational setting where participants were exposed to high levels of elemental carbon and PM 10 (particulate matter with aerodynamic diameter ≤10 μm), Pavanello et al reported decreased levels of mtDNA abundance. 35 Nevertheless, these studies focused on short-term exposures, which may not capture aggregated risk due to prolonged environmental exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Normal mitochondrial function generates reactive oxygen species, and because of its proximal location, mtDNA is particularly vulnerable to oxidative damage. Effects of air pollution on mtDNA damage, including copy number variation,7 8‐hydroxy‐2′‐deoxyguanosine formation,8 and heteroplasmy,9 have been reported in human and animal studies. Recently, DNA methylation machinery was found in mitochondria,10 and mtDNA methylation levels have been shown to be associated with mitochondrial gene expression,11 which suggests possible roles for mtDNA methylation in controlling mitochondrial functions and biogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…2 Thus, the mutation rate of mtDNA has been reported to be up to 15-fold higher than for nuclear DNA in response to DNA-damaging agents 3 such as UV, cigarette smoke, benzene, and ionizing radiation. [4][5][6] It has been hypothesized that mitochondria function and mtDNA damage are involved in carcinogenesis. 7 Studies have suggested that mitochondria possibly increase the number of mtDNA copies to compensate for mtDNA damage and mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%